Augmented Reality Learning Media Based on Understanding by Design: Improving Elementary School Students’ Attitudes of Tolerance - Sartika Ayu; Yessy Yanita Sari (Universitas Pendidikan Ganesha, 2025)
Mutual respect among elementary school students remains low, indicated by a lack of appreciation for differences and the emergence of behaviors that do not reflect tolerance. This study aimed to develop and evaluate the effectiveness of augmented reality learning media based on understanding by design in enhancing students’ tolerance attitudes. The research employed a research and development (R&D) method using the ADDIE model and involved 30 fourth-grade students as participants. Data were collected qualitatively through observations, interviews, expert validation, and student response questionnaires, and quantitatively through validation tests, normality tests, and paired sample t-tests. The results indicated that the learning media were feasible, practical, and effective, with expert validation scores for language, content, and media each above 4.3 on a 5-point scale. Students demonstrated active engagement and improved understanding of tolerance values, while the paired t-test showed a significant increase from pre-test to post-test. The media also provided an interactive, enjoyable learning experience that students could access independently. In conclusion, the use of augmented reality learning media based on understanding by design is proven effective in enhancing students’ tolerance attitudes and represents an innovative strategy applicable in character education. The study’s implications suggest that integrating appropriate technology and pedagogy supports the internalization of tolerance values and fosters a young generation that is adaptive and appreciative of diversity.